HBM4EU chromates study - Galea, Karen S. (2021)
The EU human biomonitoring initiative, HBM4EU, aims to co-ordinate and advance human biomonitoring (HBM) across Europe. As part of HBM4EU, we presented a protocol for a multicentre study to characterize occupational exposure to hexavalent chromium (Cr(VI)) in nine European countries (HBM4EU chromates study). This study intended to collect data on current occupational exposure and to test new indicators for chromium (Cr) biomonitoring (Cr(VI) in exhaled breath condensate and Cr in red blood cells), in addition to traditional urinary total Cr analyses. Also, data from occupational hygiene samples and biomarkers of early biological effects, including genetic and epigenetic effects, was obtained, complementing the biomonitoring information. Data collection and analysis was completed, with the project findings being made separately available. As HBM4EU prepares to embark on further European wide biomonitoring studies, we considered it important to reflect on the experiences gained through our harmonised approach. Several practical aspects are highlighted for improvement in future studies, e.g., more thorough/earlier training on the implementation of standard operating procedures for field researchers, training on the use of the data entry template, as well as improved company communications. The HBM4EU chromates study team considered that the study had successfully demonstrated the feasibility of conducting a harmonised multicentre investigation able to achieve the research aims and objectives. This was largely attributable to the engaged multidisciplinary network, committed to deliver clearly understood goals. Such networks take time and investment to develop, but are priceless in terms of their ability to deliver and facilitate knowledge sharing and collaboration.